Analisis Pembentukan Portofolio Optimal dan Penentuan Nilai Risiko pada Saham Syariah - Ajeng Defi Aprilia; Ade Ali Nurdin; Muhamad Umar Mai (Journal of Applied Islamic Economics and Finance, 2021)
The purpose of this research is to determine the optimal portfolio formation in Islamic stocks on the Jakarta Islamic Index (JII) which is listed on the Indonesia Stock Exchange with a single model. Then measure the risk value that may occur and be accepted by investors using the Value at Risk (VaR) method with the Exponentially Weighted Moving Average (EWMA) approach. By using the Single Index Model, 5 stocks are selected and form an optimal portfolio, namely ASII, ICBP, TLKM, UNTR and UNVR.